RANCANG BANGUN SISTEM OKSIDASI LAPISAN TIPIS SEMIKONDUKTOR OKSIDA LOGAM UNTUK SENSOR GAS CO - Bambang Herlambang (Pusbindiklat - LIPI, 2010)
In this research, manufacture of oxidation system for oxidation process of metal thin film has been done. This process is required to obtain metal oxide semiconductor which can be used as CO sensor. The system comprises furnace, temperature sensor, temperature controller, O2 gas tube, and flow meter. The system developed was then tested to know its performances by observing its temperature conditioning and controlling ability the furnace. The data processing results show that the value shown by the K thermocouple and digital temperature transducers can be stated with equation y = 0.9974x – 1.4339 where x is the value shown by type K thermocouple and y is the value shown by digital temperature transducers, while standard error is 2.24%. X-Ray analysis on Sn thin film samplesthat were oxidized for 12 and 24 hours at 400°C show that SnOx contents increase with increasing of oxidizing duration. Samples oxidized for 24 hours has little increasing of SnOx content than sample with oxidation for 12 hours due to oxidation saturation occurred on thin film surface.